Update Modeling and Decision Analysis of Product Data Based on MATLAB - Wu, Zhaomei; Li, Gang (LPPM STIKI Malang, 2024)
In this paper, the automatic pricing and replenishment decision of vegetable commodities in fresh supermarket are quantitatively analyzed, and a revenue maximization model of vegetable commodities is established, which considers demand forecast, sales revenue, cost plus pricing, replenishment quantity and sales mix. Based on grey prediction and correlation analysis, this paper determined the key factors affecting the demand of vegetable commodities. A model of vegetable commodity income maximization was established by using linear programming, and specific schemes of different replenishment and pricing levels were given. Based on historical sales data and wholesale price data, the daily replenishment volume and pricing strategy of each category and item in the coming week are provided. According to the actual situation, the limit of sales space and the upper limit of production capacity are determined.